Randomized clinical trial of astaxanthin supplement on serum inflammatory markers and ER stress‐apoptosis gene expression in PBMCs of women with PCOS - Jabarpour, Masoome; Amidi, Fardin; Aleyasin, Ashraf; Nashtaei, Maryam Shabani; Marghmaleki, Mojtaba Saedi (Journal of cellular and molecular medicine, 2024)
Polycystic ovarian syndrome (PCOS) is related to pro‐apoptotic and pro‐inflammatory conditions generated by Endoplasmic reticulum (ER) stress. This study aimed to determine the effect of Astaxanthin (ASX), as carotenoid with potent antioxidant and anti‐inflammatory properties, on serum inflammatory markers, apoptotic factors and ER stress‐apoptotic genes in peripheral blood mononuclear cells (PBMCs) of women with PCOS. This randomized, double‐blind clinical trial included 56 PCOS patients aged 18–40. For 8 weeks, subjects were randomly assigned to one of two groups: either 12 mg ASX (n = 28) or placebo (n = 28). Real‐time PCR was used to quantify gene expression associated with ER stress‐apoptosis in PCOS women's PBMCs. The levels of TNF‐α, IL18, IL6 and CRP were determined by obtaining blood samples from all patients before and after the intervention using Enzyme‐linked immunosorbent assay (ELISA). Also, the levels of active caspase‐3 and caspase‐8 were detected in the PBMC by ELISA kit. Furthermore, we evaluated the efficacy of ASX on disease symptoms. Following the 8‐week intervention, ASX supplementation was able to reduce the expression of GRP78 (p = 0.051), CHOP (p = 0.008), XBP1 (p = 0.002), ATF4 (0.038), ATF6 (0.157) and DR5 (0.016) when compared to the placebo. However, this decrease was not statistically significant for ATF6 (p = 0.067) and marginally significant for GRP78 (p = 0.051). The levels of TNF‐α (p = 0.009), IL‐18 (p = 0.003), IL‐6 (p = 0.013) and active caspase‐3 (p = 0.012) were also statistically significant lower in the therapy group. However, there was no significant difference in CRP (p = 0.177) and caspase‐8 (p = 0.491) levels between the treatment and control groups. In our study, ASX had no significant positive effect on BMI, hirsutism, hair loss and regularity of the menstrual cycle. It appears that ASX may benefit PCOS by changing the ER stress‐apoptotic pathway and reducing serum inflammatory markers; however, additional research is required to determine this compound's potential relevance.